Structural Changes in Agriculture of Ukraine: Results and Perspectives - Moroz, Serhiy (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
The paper examines structural changes in the Ukrainian agriculture during the reform period. The tendencies in the agricultural sector and directions of its transformations are considered. It has been concluded that the multifunctional model of agriculture should be implemented in Ukraine, because it can create good opportunities for an increase in the competitiveness of the agricultural sector, a solution of socio-economic issues of the rural areas and a provision of an integrated development of rural areas in the long-term perspective.